Ex-post consequences of participatory foresight processes in agriculture. How to help dairy farmers to face outcomes of collective decisions planning? - Dernat, Sylvain; Etienne, Rebecca; Hostiou, Nathalie; Pailleux, Jean-Yves; Rigolot, Cyrille (Frontiers in Sustainable Food Systems, 2022)
The analysis of the consequences of participatory foresight in agriculture over the long term is little studied in the scientific literature. In particular, it questions how farmers deal with the proposed scenarios afterwards and the modalities of their implementation. This article aims to overcome this by proposing an ex-post analysis of a foresight process with New World Kirkpatrick's Model (NWKM) carried out in mid-2018 in the Fourme de Montbrison cheese Protected Designation of Origin (PDO) area in the Massif Central (France). A set of 24 semi-structured interviews was conducted in spring and summer 2020 with the dairy farmers involved. Moreover, collective organization has been investigated through participatory observation and an analysis of project's progress reports until March 2021. The results show that while the engagement of farmers in the collective dynamic remains, it needs to be continuously rebuilt over time, particularly in order to overcome the effects of social risk-taking and insecurity that farmers must face. In addition, the place of stakeholders needs to be clarified. The article proposes a series of guidelines based on the project's experience and the “Monitor and Adjust” approach of the NWKM. It demonstrates the importance of establishing long-term follow-ups to foresight approaches to encourage farmers into action.